Bentuk Pertunjukan Kesenian Reog Ponorogo di Desa Sumber Rahayu Kecamatan Rambang Kabupaten Muara Enim - Oliasari, Oliasari; Elvandari, Efita; Firmansyah, Dedy (Institut Teknologi Pendidikan Indonesia, 2022)
Reog Ponorogo Singomodo Guyub Rukun is one of several arts that exist in the Sumber Rahayu community. Reog Ponorogo is an art form that is still alive and developing in the Muara Enim district, one of which is in the village of Sumber Rahayu. The problem in this study is how the form of the Reog Ponorogo Art performance in Sumber Rahayu Village, Rembang District, Muara Enim Regency. The purpose of this study was to find out and describe the form of the Reog Ponorogo art performance in Sumber Rahayu Village, Rembang District, Muara Enim Regency. The research method used by the author is qualitative. Thesource of the data in this study is several artists in the arts of Reog Ponorogo, Singo, easy to get along with. By using data collection techniques namely observation interviews and documentation.